KONTRIBUSI KELENTUKAN PERGELANGAN TANGAN DENGAN HASIL LEMPARAN BEBAS (FREE THROW) PADA SISWA EKSTRAKURIKULER BOLA BASKET SMA BABUSSALAM - Yusuf Setiyo Darmo; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to reveal about: the contribution of wrist flexibility with the results of the Babussalam High School basketball free throw. In this study the correlational research was used. The population in this study was all Basketball Ball extracurricular members in 16 Babussalam High School. In this research, using total sampling, all 16 extracurricular members of Basketball in Babussalam High School. Based on the results of research and data processing using statistical research procedures, it was concluded that for the relationship of variable X to variable Y obtained (0.975)> r table (0.497), t count (16.41)> t table (1.746). Contribution of wrist shape to the results of free throws Basketball extracurricular participants at Babussalam High School who were tested with a Determination Coefficient (KD) obtained a contribution of 95%, while the remainder was influenced by other variables. In this study, the results of this coefficient of determination showed a fairly large value of 95%, with the meaning of the contribution word or contribution of variable wrist elasticity by 95% and contributions from other variables only around 5%. The hypothesis was accepted at a significant level α = 0.05. In other words, there is a significant contribution between wrist detachment and free throw results of basketball extracurricular participants at Babussalam High School.Key Words: Flexibility, Free Throw